Deblurring images matrices, spectra, and filtering - Hansen, Per Christian 1957-; Nagy, James G.; O'Leary, Dianne (Fundamentals of algorithms, 2006)
Describes the deblurring algorithms and techniques collectively known as spectral filtering methods, in which the singular value decomposition, or a similar decomposition with spectral properties, is used to introduce the necessary regularization or filtering in the reconstructed image. The concise MATLAB implementations described in the book provide a template of techniques that can be used to restore blurred images from many applications